Pengaruh Kepuasan dan Kepercayaan terhadap Kesetiaan Nasabah BNI Tapenas di Bank BNI Cabang Probolinggo - Sukarsono, Bambang (Jurnal Aplikasi Manajemen, 2008)
This research aim to test influence of satisfaction to trust of Client, testing influence of sarisfaction to faithfulness of Client, testing influence of trust to faithfulness of Client and to test dominant factor among trust and satisfaction influencing faithfulness of Client of BNI Tapenas. This Research is conducted by in Sub-Province of Probolinggo by taking case al Bank of BNI Branch Probolinggo. Population of this research is all client which saving its money in Bank of BNI Branch Probolinggo in the form of BNI TAPENAS a number of 104 people. From amount of population, is later then determined by size measure of sample counted 100 people, with consideration that amount of the sampel have the including big sample. Sampling technique the used is sampling random simple. As for Technique analyzer the used is Simultaneous Eguation two phase. Pursuant to result of analysis and also examination of hypothesis which [is] can be pulled by conclusion that perception of employees about satisfaction of client in the form of expectation or desire and accepied service have fulfilled better posed at with score mean 3,84, while perception of employees about trust of client in the form of reaction of client as accumulation from with refer to its assessment to accepted service it showing with score mean 3,64 and perception of employees about faithfulness of client posed at with client again save its money in BNI Branch Probolinggo and give recommendasion [at] family, other society and neighbor, posed at with score mean 3.94. From result of examination of hypothesis can be concluded that variable satisfaction of client have influence by significance to variable trust of client: variable satisfaction of client have influence by significance to variable faithfulness of client, variable trust of client have influence by significance to variable faithfulness of client. From two variable that is satisfaction and trust of most having an effect on client to faithfulness [is] client fasting variable. Of the Conclusion suggested in the effort improving faithfulness of client, [party/ side] of BNI require to develop build to improve promotion about Tapenas so that the amount of client of Tapenas also mount, improving the quality of and service.